Replacing Sedentary Behavior with a Light Intensity Physical Activity in the Homes of Older Adults - (:unkn) unknown (My University, 2018)
Aging is positively correlated with time spent in sedentary behavior (SB), which has been found to be linked to premature mortality, cardiovascular disease risk, and functional limitations. Moderate-to-vigorous-intensity physical activity (MVPA) is a potent stimulus for preventing and improving functional limitations in older adults, but less than 17% of the older adult population meets the recommended PA guidelines. While increased time spent in SB is detrimental to health in all, the impact among those that are physically inactive appear to be most pronounced. Recent evidence suggests increasing light-intensity physical activity (LPA) in these populations may provide health benefits and could be a more practical approach for older adults. The purpose of this dissertation project is to identify safe, effective, and practical evidence-based approaches to reduce SB to maintain or improve physical function in late life. Therefore, the aims of this dissertation project are three fold: 1) to identify the impact of replacing time spent in SB with physical activity on measures of physical function in community-dwelling older adults, 2) identify the feasibility of using a seated portable elliptical device (SED) in the homes of older adults, and 3) determine the effectiveness of using a SED to replace time spent in SB with a LPA and explore the impact on measures of physical function in older adults. An isotemporal substitution regression model identified that replacing as little as 30 minutes of SB with LPA led to significant improvements in walking speed. Meanwhile, replacing up to 60 minutes of SB with LPA led to larger magnitudes of improvement which approached clinical relevance. Further, supplementing LPA with MVPA progressively increased the improvements in a battery of functional assessments. Interventions to reduce SB have come with difficulty and methods to purposefully replace SB with PA should be developed to test the validity of the findings from these novel statistical models. A seated elliptical pedaling device (SED) was used to purposefully target reducing SB and replacing with LPA, while allowing participants to maintain the enjoyment of their typically passive activity in their home. A one week trial study identified that there was no difference in the ability of older adults to accumulate between 15 to 60 minutes of pedaling per day. Further, there was high acceptability among all participants that were randomly assigned to either 15, 30, 45, or 60 minutes per day pedaling groups. This led to the development of an 8-week pilot randomized controlled trial using the SED. In this trial, the intervention was effective at replacing SB with LPA as identified by a group by time interaction effect. Specifically, the elliptical group (EG) experienced a significant 7.3% (p = 0.003) reduction in daily SB and 7.1% (p = 0.002) increase in LPA between baseline and follow-up testing compared to no significant difference in the control group (CG). Participants suggested improvements in function, but small effect sizes and sample sizes did not produce significant improvements in measures of physical function. Introducing a SED during passive activities in the home is a feasible and effective approach at reducing daily SB in older adults. While some of the functional tests did exhibit ceiling effects among those that were high functioning at baseline, subjective responses from individuals of lower functioning suggest the potential for impacting the QOL of those that have difficulty performing ambulatory activities. Future investigations using the SED should be directed toward longer intervention periods, with larger sample sizes, and among individuals of various levels of functional ability and life circumstances.
Keywords: aging; function; pedaling; sitting